Synbiotic yogurts and the elderly - Sivieri, Katia [UNESP]; Freire, Fernanda C. [UNESP]; Lopes, Natalia P. [UNESP]; Shiraishi, Christiane T.D. [UNESP]; Pires, Ana Carolina M.S. [UNESP]; Lima, Ana Carolina D. [UNESP]; Zavarizi, Adriana C.M. [UNESP]; Sgarbosa, Letícia [UNESP]; Bianchi, Fernanda [UNESP] (Elsevier, 2017)
Many problems can seriously affect the health of the elderly. Health promotion practices should focus on dietary intake of functional foods. Several dietary strategies, including an increase of fiber intake and the consumption of probiotic and synbiotic foods including synbiotic yogurt, have been associated with health improvement. Generally, yogurt consumption has been associated with health benefits in different populations. However, limited information is available on the nutritional and health attributes of synbiotic yogurt in older adults. In this context, more intervention trials with probiotics and/or prebiotics or synbiotics are needed to elucidate the mechanisms of action involved and to definitely demonstrate their effectiveness in the elderly. Therefore this chapter will focus on the potential benefits of pro-, pre-, and synbiotic foods, including synbiotic yogurt, to improve and maintain health and wellbeing in aged persons.
Keywords: Ageing; Health; Prebiotics; Probiotics; Synbiotics; Yogurt